The Role of Hippocampal and Medial Prefrontal Interactions in the Estrogenic Regulation of Memory - (:unkn) unknown (My University, 2017)
Dendritic spine plasticity is thought to be essential for the formation and storage of memories. The sex-steroid hormone 17-estradiol (E2) increases dendritic spine density in 2 brain regions necessary for memory formation, the dorsal hippocampus (DH) and medial prefrontal cortex (mPFC), but the mechanisms through which it does so remain largely unknown. Further, the extent to which these brain regions interact to mediate E2’s effects on memory is also unclear. Recently, we found that infusion of E2 directly into the DH also increases dendritic spine density in the DH and mPFC, and that these effects depend upon rapid activation of the extracellular signal-regulated kinase (ERK) and mammalian target of rapamycin (mTOR) cell-signaling pathways in the DH (Tuscher et al., 2016). These intriguing findings highlighted a previously unexplored interaction between the DH and mPFC that may have important implications for understanding how E2 regulates memory. As such, these data led us to question what the role of the mPFC is during object memory formation, and whether interactions between the DH and mPFC are necessary for the E2-induced memory enhancements we have previously observed in our object memory tasks (Fernandez et al., 2008, Boulware et al., 2013, Fortress et al., 2013). Therefore the overall goal of the dissertation was to examine the role of the DH and mPFC in object memory consolidation both in the presence and absence of exogenous E2 infusions, and to examine how E2 regulates spine density changes in these regions, which may ultimately strengthen the synaptic connections involved in the formation of such memories. To this end, we first utilized inhibitory Designer Receptors Exclusively Activated by Designer Drugs (DREADDs) to inactivate the DH, the mPFC, or both brain regions simultaneously immediately after novel object training to assess the role of each of these regions individually and in combination during object memory consolidation. Next, we asked whether E2 can act directly in the mPFC to enhance object memory consolidation and increase spine density in the mPFC and DH. Finally, we combined DREADD-mediated inhibition of the mPFC with direct infusion of E2 into the DH to examine whether DH-mPFC interactions are necessary for the beneficial mnemonic effects of DH infused E2. Our results collectively suggest that individual and simultaneous activation of both the DH and mPFC is required for the successful consolidation of object recognition and spatial memories. We also found that infusion of E2 directly into the mPFC increases mPFC apical spine density and facilitates object memory consolidation. Finally, we demonstrate that activation of the mPFC is necessary for the memory-enhancing effects of DH-infused E2. Together, these studies provide critical insight into how the DH and mPFC work in concert to facilitate E2-mediated memory enhancement in female mice. Further, this work will enable future studies investigating circuit and cellular-level questions regarding how E2 mediates cognition across the lifespan.